Network sharing: a proposal for knowledge exchange in pandemic times - Campos, Fernanda Araujo Coutinho; Cavalcanti, Ana Paula Campos (Revista Docência do Ensino Superior, 2020)
The objectives of this work are to report on and reflect on the experiences of the group "Educações em Rede" (Network Education). Formed by teacher-researchers, it was proposed as a space for continuing education for teachers at different levels and for networking, as a response to face educational challenges in the face of the Covid-19 pandemic. The actions carried out consisted of webinars transmission; production of tutorials and publication of articles to assist teachers in the theoretical, methodological and technical difficulties emerging in this context. The central motivation of "Educações em Rede" was to debate and share knowledge with different actors from different parts of Brazil and the world, establishing themselves as a learning network. The analyzed data show that the public was essentially composed of Brazilian teachers, from 30 to 45 years old, in search of an accessible space for debate and non-formal training in the use of technologies applied to education.